THE FORM AND MEANING OF NAHYI IN THE QURAN SURAH AL-BAQARAH: A REVIEW OF ROMAN JAKOBSON’S SEMIOTICS / BENTUK DAN MAKNA NAHYI DALAM AL-QUR’AN SURAH AL-BAQARAH: TINJAUAN SEMIOTIKA ROMAN JAKOBSON - Eghy Farhan Nugraha (Lughawiyah: Journal of Arabic Education and Linguistics, 2022)
This study aims to determine the form and meaning of nahyi in Al-Quran Surah Al-Baqarah based on the perspective of Roman Jakobson's semiotic theory of communication. Descriptive qualitative was used as the method of this research. Al-Qur’an surah Al-Baqarah verse 22, 41, 42, 132, and 147 were the source of the data. The study’s findings indicated that the message’s sender is Allah SWT, the recipient is human, and the code is fi’il nahyi. The messages from nahyi contained in surah Al-Baqarah verses are not the same. In verse 132, the message is irsyad (guidance), whereas in verses 22, 41, 42, and 147, the message is tahdzir (threat). This demonstrates that nahyi does not only mean a prohibition, but also means giving instructions. The nahyi context varies as well. The context is situational context in verses 22, 41, 132, and 147, and cultural context in verse 42. Therefore, it is important for Arabic learners to understand the forms and meanings of nahyiin order to distinguish them when they appear in spoken or written Arabic.